The study of host–microbiome (co)evolution across levels of selection - Koskella, Britt (Philos Trans R Soc Lond B Biol Sci, 2020)
Microorganismal diversity can be explained in large part by selection imposed from both the abiotic and biotic environments, including—in the case of host-associated microbiomes—interactions with eukaryotes. As such, the diversity of host-associated microbiomes can be usefully studied across a variety of scales: within a single host over time, among host genotypes within a population, between populations and among host species. A plethora of recent studies across these scales and across diverse systems are: (i) exemplifying the importance of the host genetics in shaping microbiome composition; (ii) uncovering the role of the microbiome in shaping key host phenotypes; and (iii) highlighting the dynamic nature of the microbiome. They have also raised a critical question: do these complex associations fit within our existing understanding of evolution and coevolution, or do these often intimate and seemingly cross-generational interactions follow novel evolutionary rules from those previously identified? Herein, we describe the known importance of (co)evolution in host–microbiome systems, placing the existing data within extant frameworks that have been developed over decades of study, and ask whether there are unique properties of host–microbiome systems that require a paradigm shift. By examining when and how selection can act on the host and its microbiome as a unit (termed, the holobiont), we find that the existing conceptual framework, which focuses on individuals, as well as interactions among individuals and groups, is generally well suited for understanding (co)evolutionary change in these intimate assemblages. This article is part of the theme issue ‘The role of the microbiome in host evolution’.